The Role of Control Environment (CE) in the Public Sector in Preventing Fraud: A Literature Study - Harahap, Ludwina; Isgiyarta, Jaka (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This paper aims to conduct a literature study on the role of the CE in preventing fraud. Undoubtedly, weak internal controls (IC) and CE are the factors that cause various cases of fraud to occur, such as corruption, collusion, bribery, and various unethical behaviors.. The COSO IC Framework and previous studies explicitly state that the CE is the primary basis for building a strong IC system, and the leader or supervisor is a central figure in realizing the formation of a strong CE. However, from several previous studies, not much has examined the role of the CE on the effectiveness of ICs in preventing fraud. The method used is to enter keywords in the search engine, consisting of "corruption, fraud, CE, corruption in the public sector, unethical behavior, public sector". Databases like Scopus, Emerald, Google Scholars, Scihub, and Proquest are utilized as search tools to discover pertinent research in this specific field. The results show that several previous studies using quantitative and qualitative methods to examine the effectiveness of CE and the role of leaders in creating a strong CE to prevent and reduce fraud. The study contributes general knowledge and practical insights of the role of CE and the role of a leader to enforce CE.